Evaluation of the influence of encapsulated mineral fertilizers on plant growth kinetics - Shkvirko, Oksana; Grechanik, Ruslan; Malovanyy, Myroslav; Tymchuk, Ivan; Nagurskyy, Oleg; Lutek, Wojciech (Видавництво Львівської політехніки, 2024)
The work investigated the effect of encapsulated mineral fertilizers on the growth and development of plants for 45 days. As a mineral fertilizer, nitroammophoska was used, which was encapsulated by a shell of different compositions: sample KD1 – a mixture of polystyrene, lignin, and carbon; sample KD2 – a mixture of polystyrene, lignin, and zeolite. The bioindication method was used to determine the effect of encapsulated mineral fertilizers on plant growth kinetics. Based on the study's results, the average rate of germination of ryegrass in the experimental samples and the average rates of the main plant parameters (stem height, root length, plant weight) were determined. It was established that the highest rate of germination was in the sample with encapsulated mineral fertilizer KD1 — 100%, and the lowest in the sample GD – 85 %. The highest average indicators of measurement of the main parameters of ryegrass were in samples KD1 and KD2. The highest average indicators of measurement of the main parameters of ryegrass were in samples KD1 and KD2, and the lowest in the control sample (soil). It was established that on the 45th day, the mineral fertilizer in the KD1 sample was fully absorbed by the plants.
Keywords: encapsulated mineral fertilizer; bioindication; granular fertilizer; plant parameters; biological reclamation